Polychlorinated biphenyl and polybrominated diphenyl ether profiles in serum from cattle, sheep, and goats across California. (August 2017) - Sethi, S.; Chen, X.; Kass, P.H.; Puschner, B.
Abstract: It has been previously been shown by our lab and others that persistent organic pollutants, such as polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs), are contaminants in milk produced for human consumption. To further this research we determined the concentration of 21 PCB and 14 PBDE congeners in livestock serum, mainly bovine, across California. Congeners were extracted from serum using solid phase extraction (SPE), cleaned up by silica cartridge and quantified using gas chromatography-triple quadruple mass spectrometry. We detected significant differences among species and the production class of cattle (beef or dairy). The sum of all 21 PCB congeners (ΣPCBs) in caprine and ovine sera had a mean value of 9.26 and 9.13 ng/mL, respectively, compared to 3.98 ng/mL in bovine sera. The mean value for the sum of all 14 PBDE congeners (ΣPBDEs) in caprine and ovine sera was 2.82 and 2.39 ng/mL, respectively, compared to 0.91 ng/mL in bovine sera. Mean ΣPCBs in dairy cattle was 5.92 ng/mL compared to 2.70 ng/mL in beef cattle. Mean ΣPBDEs in dairy cattle was 1.33 ng/mL compared to 0.70 ng/mL in beef cattle. There were no regional differences in the ΣPCBs or ΣPBDEs in cattle distributed across California. These results highlight the fact that livestock are still being exposed to these pollutants yet little is known about where this exposure may be coming from. Graphical abstract: Highlights: Caprine and ovine sera contain higher levels of PCBs and PBDEs than sera of bovine. Dairy cows have higher levels of PCBs and PBDEs than cows used in beef production. A non-legacy PCB, PCB 11, was detected at quantifiable levels in all livestock sera. There are no significant regional differences in the sum concentration of PCBs and PBDEs in bovine sera in California.